Key Principles in Children’s Healthy Nutrition in Schools: A Cross-National Review - Gorelova, Jeanneta; Neustroev, Sergey; Mindzaeva, Eteri; Beshenkov, Sergey; Arinushkina, Anna (Journal of History Culture and Art Research, 2019)
The paper presents contemporary data of foreign and Russian researchers on the healthy nutrition of schoolchildren. An analysis of the existing forms and principles of school catering is provided; school rations around the world, different approaches to their formation, and new school nutrition standards in the USA and Eastern Europe are described and discussed. The authors focus on the implementation of the National Government programs on the organization of school healthy nutrition in foreign countries. Original research data collected by the Russian scientists on students’ taste preferences are also provided in the paper. Our review clearly indicates a number of products that are offered in a school menu do not meet students’ taste preferences. The authors also note that there is no continuity between home and school meals. This determines the need to better educate parents, children, and teachers about modern principles and skills of healthy nutrition, to take into account schoolchildren’s food preferences, to promote learning to use a “school-family menu” principle. On the basis of the conducted research, the authors recommend creating an effective model of school feeding in the Russian Federation. On the one hand, this model takes into account local experience, while on the other hand, this model is quite universal (consequently, it is applicable in any foreign country, not only in Russia).